Original paperRelation between coronary plaque calcium deposits as described by computed tomography coronary angiography and acute results of stent deployment as assessed by intravascular ultrasound - Pregowski, Jerzy; Jastrzebski, Jan; Kępka, Cezary; Kruk, Mariusz; Ciszewski, Michał; Wolny, Rafał; Zalewska, Joanna; Chmielak, Zbigniew; Karcz, Maciej; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Introduction : The findings from intravascular ultrasound studies on the impact of calcium deposits on the results of stent implantation are conflicting. Aim: To evaluate whether calcium deposits as assessed by (CTCA) influence results of stent deployment. Material and methods: The study population comprised 60 patients (43 male; age 64.2 ±8.6 years) who underwent CTCA before stent implantation. Lesion calcium score, total calcium length, and maximal area and maximal thickness of calcium deposits within the lesion segment were assessed. Plaques were divided into those with calcium score  median (group 1), calcium score < median (group 2), and without calcium (group 3). Intravascular ultrasound (IVUS) was performed after attainment of optimal angiographic results of the stent procedure. Focal and diffuse stent expansion was defined as either minimum stent area (MSA) or mean stent area over the length of the stent divided by reference lumen area. Results : The proximal reference segments of lesions with higher calcium score contained a larger plaque burden (47 ±12% vs. 41 ±9% vs. 34 ±18%, p = 0.02) – respectively for groups 1, 2, and 3. Positive correlation was observed between lesion calcium score and frequency of post-dilation (R = 0.28, p = 0.03). There was no difference in focal stent expansion (71 ±14% vs. 65 ±15% vs.71 ±15%, p = 0.3) or diffuse stent expansion (92 ±30% vs. 85 ±30% vs. 93 ±38%, p = 0.7) comparing groups 1, 2, and 3. Lesion calcium score, total length of calcium, and maximum area and thickness of calcium deposits did not correlate with focal or diffuse stent expansion. Conclusions : Lesions with a higher CTCA calcium score had larger reference plaque burden after stent implantation and more likely required post-dilation, but final stent expansion as assessed by IVUS was not affected by the amount of CTCA calcium provided an angiographically optimal result was achieved.